Methods of monitoring the training and match load and their relationship to changes in fitness in professional youth soccer players - Akubat, I.; Patel, E.; Barrett, S.; Abt, G. (Journal of Sports Sciences, 2012)
Previous studies examining methods of monitoring the training and match load in soccer players have simply compared those methods to each other, not to changes in fitness. Training and match load measures from nine professional youth soccer players were collected for a period of six weeks. A lactate threshold test was conducted before and after this period. Mean weekly training and match load as determined by session-RPE, Banister's TRIMP, Team TRIMP and individualised TRIMP (iTRIMP) were correlated with each other, percentage changes in the velocity at 2 mmol/L (vLT) and 4 mmol/L (vOBLA) blood lactate concentration, and heart rate at 2 mmol/L (LTHR) and 4 mmol/L (OBLAHR). There were no significant changes in fitness across the six weeks: vLT (p = 0.54), vOBLA (p = 0.16), LTHR (p = 0.51) and OBLAHR (p = 0.63). Banister's TRIMP was significantly correlated with session-RPE (r = 0.75; p = 0.02) and Team TRIMP (r = 0.92; p < 0.001). The percentage change in vLT was significantly correlated to mean weekly iTRIMP (r = 0.67; p = 0.04). The results suggest that an individualised measure of internal load (iTRIMP) related better than other methods to changes in vLT in professional youth soccer players.